The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/anu.13100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rosemary (Rosmarinus officinalis) extract on growth, blood biochemistry, immunity, antioxidant, digestive enzymes and liver histopathology of rainbow trout,Oncorhynchus mykiss

Abstract: This research was designed to determine the effects of rosemary (Rosmarinus officinalis) extract on growth, blood biochemistry, immunity, antioxidant, digestive enzymes and liver histopathology of rainbow trout. In a 40‐day diet experiment, rainbow trout was fed with the experimental diets containing 0.4, 0.7, 1 and 3 g/kg of rosemary. 0.4 and 0.7 g/kg rosemary extracts had no significant effect on all parameters studied (p > .05). The growth performance (SGR and WG) and feed utilization (FCR and FER) of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 59 publications
3
11
0
Order By: Relevance
“…In our experiments, we found that the ALT, AST, and LDH were significantly lower in Group 3 compared with Group 2. This results is in agreement with the findings of Karataş et al [25], and Almakhatreh et al [26]. R. Officinalis extract greatly lowered the blood-brain barrier permeability disruption and injuries, moreover, it lessens the effect of the myocardial infarction and neurological deficit scores after focal Ischemia-Reperfusion.…”
Section: Resultssupporting
confidence: 93%
“…In our experiments, we found that the ALT, AST, and LDH were significantly lower in Group 3 compared with Group 2. This results is in agreement with the findings of Karataş et al [25], and Almakhatreh et al [26]. R. Officinalis extract greatly lowered the blood-brain barrier permeability disruption and injuries, moreover, it lessens the effect of the myocardial infarction and neurological deficit scores after focal Ischemia-Reperfusion.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, a decrease in ALT and AST by dietary antioxidants in rainbow trout and other salmonids have been reported by other researchers (e.g. Darabitabar et al, 2016;Kamgar et al, 2013;Karataş et al, 2020;Naderi et al, 2017;Řehulka, 2000;Shekarabi et al, 2020). In the present study, the level of ALT in bacilli treatment was lower than other treatments and control.…”
Section: Antioxidant Enzymessupporting
confidence: 83%
“…Also, our results showed that fish treated with rosemary extract demonstrated a lower ALT activity, but no significant difference in AST level was seen compared to control fish. Karataş et al (2020) exhibited no significant change in AST and ALT activities in trout fed rosemary extract at 400 and 700 mg kg, while diets containing higher dosage of rosemary extract decreased the enzymes activities.…”
Section: Antioxidant Enzymesmentioning
confidence: 85%
“…Because of such remarkable biological activities, RA has gained considerable attention for use in pharmaceutical and functional food industries (Amoah et al, 2016). Consequently, the demand for RA has increased considerably, which has motivated the development of effective extraction methods from its natural sources.Rosemary (Rosmarinus officinalis L.) is an aromatic evergreen herb belonging to the Lamiaceae family (Karataş et al, 2020).…”
mentioning
confidence: 99%
“…Rosemary (Rosmarinus officinalis L.) is an aromatic evergreen herb belonging to the Lamiaceae family (Karataş et al, 2020).…”
mentioning
confidence: 99%